Democracia, xenofobia e interseccionalidad : Democracy, Xenophobia and Intersectionality - Estay Sepúlveda, Juan Guillermo; Barrientos-Baéz, Almudena; Mancina-Chávez, Rosalba (Universidad del Zulia, 2022)
Democracy is at a crossroads before the powers of the new technologies and the totalitarian, fundamentalist and fundamentalist groups that with their hate speech are undermining its pillars. Intersectionality is a new way of deepening democracy abysmally and leading it to a century of respect for the other and the other, under the aegis of multiculturalism and the projection of an open society.